2014
DOI: 10.1080/17509653.2014.943316
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of innovation concepts in Portuguese manufacturing companies

Abstract: This paper focuses on the diffusion of innovation concepts in Portuguese manufacturing companies. Based on the literature, the concepts of technical and non-technical innovations are explored and three purposes guide our study: (i) to what extent technological and organizational innovation concepts are diffused in Portuguese manufacturing companies; (ii) how the use of technological innovation concepts are interrelated with the use of organizational innovation concepts; and (iii) to what extent Portuguese comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, original equipment manufacturer designers do not make full use of design opportunities, and the chance of equipment transformation may be significantly underestimated. From the innovation conceptions, do Do Rosario Cabrita et al (2015) collected data from 62 companies and found that Portuguese manufacturing companies are more organizationally innovation-oriented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, original equipment manufacturer designers do not make full use of design opportunities, and the chance of equipment transformation may be significantly underestimated. From the innovation conceptions, do Do Rosario Cabrita et al (2015) collected data from 62 companies and found that Portuguese manufacturing companies are more organizationally innovation-oriented.…”
Section: Literature Reviewmentioning
confidence: 99%